Sacrococcygeal chordoma presenting as a retro rectal tumour - Chigurupati, Pragnya (Elsevier, 2014)
INTRODUCTION: Chordomas are rare, slow growing, locally destructive bone tumours arising from the notochord. PRESENTATION OF CASE: Presenting a case of a 65 year old man, who presented with complaints of swelling on the right lower back for 1 year associated with pain. On, physical examination, a swelling measuring 5 cm × 4 cm was noted in the lower back with posterior wall indentation on per rectal examination. MRI revealed a mass lesion involving the sacrum (s3–s4) and coccyx. FNAC showed features of a chroma. At surgery, we excised a mass from the retrorectal space and biopsy proved it to be a chondroid chordoma, a variant of chordoma. DISCUSSION: Chordomas are solid malignant tumours that arise from vestiges of the foetal notochord. Common locations are the clivus and the sacrococcygeus region. Annual incidence of these tumours is 1 in one million. MRI is the imaging modality of choice. Prognosis improves based on the age, resected margins and postoperative treatment. CONCLUSION: Here, we shall discuss the literature, variants, treatment and prognosis of this rare tumour.